Evidence for familial aggregation of hand, hip, and spine but not knee osteoarthritis in siblings with multiple joint involvement: the GARP study. Issue 3 (30th September 2004) - Riyazi, N; Meulenbelt, I; Kroon, H M; Ronday, K H; Hellio le Graverand, M-P; Rosendaal, F R; Breedveld, F C; Slagboom, P E; Kloppenburg, M
Abstract : Objective: To evaluate whether familial aggregation of osteoarthritis differs by joint site in a sibling pair study (GARP) of patients with osteoarthritis at multiple sites. Subjects: White Dutch probands aged 40 to 70 years and their siblings with primary osteoarthritis at multiple sites. Methods: The diagnosis of knee, hip, and spine osteoarthritis was based on a combination of pain or stiffness on most days of the previous month and osteophytes or joint space narrowing on x ray. Hand osteoarthritis was defined by ACR criteria. Odds ratios (OR) were calculated for siblings and probands sharing disease in the same joints. Results: 191 sibling pairs were included (85% women; mean age 60 years). In the probands, osteoarthritis was present in spine (76%), hands (77%), knees (37%), and hips (26%). The most common combinations in probands were spine–hand (59%), spine–knee (27%), and hand–knee (25%). The OR adjusted for age, sex, and body mass index for siblings to be affected in the same joint sites as the proband were increased in osteoarthritis of the hand (OR = 4.4 (95% confidence interval, 2.0 to 9.5)), hip (OR = 3.9 (1.8 to 8.4)), spine (OR = 2.2 (1.0 to 5.1)), hip–spine (OR = 4.7 (2.1 to 10.4)), and hand–hip (OR = 3.4 (1.1 to 10.4)). Siblings of probands with osteoarthritis in the knee did not have an increased likelihood of knee osteoarthritis. Conclusions: In middle aged patients with familial osteoarthritis at multiple sites, familial aggregation of osteoarthritis was most striking for hand and hip but remarkably absent for the knee.